Three-dimensional microarchitecture of entheseal changes: preliminary study of human radial tuberosity - Berthon, William; Rittemard, Charlotte; Tihanyi, Balázs; Pálfi, György; Coqueugniot, Hélène; Dutour, Olivier (Acta Biologica Szegediensis, 2015)
Entheseal changes (EC), alterations at insertion sites on the bones, may be related to mechanical stress among other causes, and are thus used for decades to reconstruct the activities of human past populations. They can be characterised by focal changes in robusticity and variable pattern of osteolysis and osteoformation observable on dry bone. This preliminary study aims to analyse the microstructural characteristics of the underlying bone to clarify the nature of the changes in bone microarchitecture reflecting the macroscopic changes identifiable on the surface of the enthesis. We studied the right radii of two Saharian adult individuals, dating from Neolithic (Hassi-el-Abiod, Mali, 7 000 years BP). One has a morphologically normal bicipital tuberosity while the second one shows EC. Micro-computed tomodensitometric acquisitions and 3D reconstructions were performed to characterise cancellous and cortical bone microarchitecture of these two entheses. 3D imaging appears relevant for studying microstructure of EC among past populations. Our methodology reveals at this preliminary step clear differences of canal network organisation of cortical bone between the two studied entheses. This work comes preliminary to a broader study on a historically and archaeologically documented population of Hungarian horse archers of the Honfoglalás or Conquest period (Xth century).